2022
DOI: 10.3390/su14095029
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking City Layouts—A Methodological Approach and an Accessibility Comparison between a Real City and the Garden City

Abstract: This article presents a comparative accessibility study between a real city and its redraft as a Garden City. The benchmarking methodology involves defining and evaluating a location-based accessibility indicator in a GIS environment for the city of Coimbra, Portugal, and for the same city laid out as a Garden City, with the same number of inhabitants, jobs, and similar number of urban facilities. The results are derived as maps and weighted average distances per inhabitant to the facilities and jobs, and show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 82 publications
(92 reference statements)
0
9
0
Order By: Relevance
“…Petras and Kveton [25] found that the impact of new road infrastructure on accessibility in the Czech Republic is strong in a few areas, whereas the impact of new road infrastructure on traffic load is relatively evenly distributed spatially. In addition, certain scholars have conducted accessibility analyses of population, hydrology, urban parks, and green spaces in cities and determined the optimal travel time for urban residents and the spatial distribution characteristics of urban green and blue spaces [26,27]. Therefore, accessibility analysis can be used to objectively evaluate the fairness and convenience of the spatial distribution of urban parks, green spaces, transportation, and residential buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Petras and Kveton [25] found that the impact of new road infrastructure on accessibility in the Czech Republic is strong in a few areas, whereas the impact of new road infrastructure on traffic load is relatively evenly distributed spatially. In addition, certain scholars have conducted accessibility analyses of population, hydrology, urban parks, and green spaces in cities and determined the optimal travel time for urban residents and the spatial distribution characteristics of urban green and blue spaces [26,27]. Therefore, accessibility analysis can be used to objectively evaluate the fairness and convenience of the spatial distribution of urban parks, green spaces, transportation, and residential buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation and analysis of the morphology of historical urban tissue is a complex matter, since there are numerous elements and factors that impact the diagnosis of urban structure quality [34][35][36][37][38][39][40]. Apart from historical research on transformations and accumulations within the analysed area, and qualitative research on urban systems, it seems advisable to perform an evaluation of land systems [41][42][43].…”
Section: Resultsmentioning
confidence: 99%
“…As one moves away from the center, urban density decreases, and scores improved. However, the outskirts have poor accessibility, few facilities, and a limited supply of public transportation [85]. Despite not being a big metropole and due to its history and urban development, Coimbra comprises several urban forms and designs that scored differently in terms of the perceived pleasantness and is a typical global north city.…”
Section: Pleasantness Scores and Socioeconomic Variables For Coimbramentioning
confidence: 99%